Multiple coronary aneurysms in a patient with neurofibromatosis type 1: case report and intravascular ultrasound of aneurysm. Issue 903 (1st January 2001) - Trevelyan, J; Been, M; Patel, R
Abstract : A 54 year old woman with neurofibromatosis type 1 (NF-1) was found to have multiple coronary aneurysms. Intraoperative intravascular ultrasound (IVUS) revealed severe coronary disease proximal to the aneurysm that had not been apparent angiographically. An IVUS picture of one of the giant coronary aneurysms is also shown. The vascular manifestations of neurofibromatosis and the causes of coronary aneurysms are reviewed.